Complex patterns of glacier advances during the late glacial in the Chagan Uzun Valley, Russian Altai. (1st October 2016) - Gribenski, Natacha; Jansson, Krister N.; Lukas, Sven; Stroeven, Arjen P.; Harbor, Jonathan M.; Blomdin, Robin; Ivanov, Mikhail N.; Heyman, Jakob; Petrakov, Dmitry A.; Rudoy, Alexei; Clifton, Tom; Lifton, Nathaniel A.; et al.
Abstract: The Southern part of the Russian Altai Mountains is recognized for its evidence of catastrophic glacial lake outbursts. However, little is known about the late Pleistocene paleoglacial history, despite the interest in such reconstructions for constraining paleoclimate. In this study, we present a detailed paleoglaciological reconstruction of the Chagan Uzun Valley, in the Russian Altai Mountains, combining for the first time detailed geomorphological mapping, sedimentological logging, and in situ cosmogenic 10 Be and 26 Al surface exposure dating of glacially-transported boulders. The Chagan Uzun Valley exhibits the most impressive glacial landforms of this sector of the Altai, with extensive lobate moraine belts deposited in the intramontane Chuja Basin, reflecting a series of pronounced former glacial advances. Observations of "hillside-scale" folding and extensive faulting of pre-existing soft sediments within the outer moraine belts, together with the geomorphology, strongly indicate that these moraine belts were formed during surge-like events. Identification of surge-related features is essential for paleoclimate inference because these features correspond to a glacier system that is not in equilibrium with the contemporary climate, but instead largely influenced by various internal and external factors. Therefore, no strict relationship can be established between climatic variables and the pronounced distal glacial extent observed in the Chagan Uzun Valley/Chuja basin. In contrast, the inner (up-valley) glacial landforms of the Chagan Uzun valley were likely deposited during retreat of temperate valley glaciers, close to equilibrium with climate, and so most probably triggered by a general warming. Cosmogenic ages associated with the outermost, innermost, and intermediate moraines all indicate deposition times clustered around 19 ka. However, the actual deposition time of the outermost moraine may slightly predate the 10 Be ages due to shielding caused by subsequent lake water coverage. This chronology indicates a Marine Isotope Stage (MIS) 2 last maximum extent of the Chagan Uzun Glacier, and an onset of the deglaciation around 19 ka. This is consistent with other regional paleoclimate proxy records and with the Northern Hemisphere glaciation chronology. Finally, this study also highlights the highly dynamic environment in this area, with complex interactions between glacial events and the formation and drainage of lakes. Highlights: A detailed paleoglacial reconstruction is presented for the Chagan Uzun Valley, Russia. Distal moraine belts are interpreted to have been formed during surge-like events. 10 Be exposure ages indicate MIS 2 last glacial maximum and deglaciation onset at ∼19 ka.